EFFECTIVENESS OF FAMILY HOPE PROGRAM IN IMPROVING ELDERLY ACCESS - Rifqi Wida Afrianda; Sri Umiyati; Elli Setiyo Wahyuni (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
This study aims to analyze the effectiveness of the Family Hope Program (Program Keluarga Harapan/PKH) in improving access to healthcare services for the elderly in Glagahsari Village, Sukorejo District, Pasuruan Regency, and to identify its supporting and inhibiting factors. This study employed a descriptive qualitative approach with a case study design. Data were collected through interviews, observations, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña. Program effectiveness was examined using William N. Dunn’s framework, covering goal attainment, adequacy, equity, responsiveness, and appropriateness, integrated with Nunes’s perspective on healthcare access. The findings indicate that PKH has effectively improved elderly access to healthcare services, although its implementation is not yet fully optimal. Supporting factors include the roles of PKH social facilitators, families, village government, healthcare workers, Integrated Health Post cadres, and cross-sector coordination. Inhibiting factors include physical limitations, chronic illnesses, transportation constraints, dependence on family support, administrative barriers, and limited health awareness among some elderly beneficiaries. Strengthening cross-sector coordination, social assistance, and adaptive healthcare services is therefore necessary to optimize the program.